Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 428868 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Anser fabalis (Latham, 1787), Larra argentata Palisot de Beauvois, 1811, Columba plumbea Sibley & Monroe, 1990, Primnoa gracilis Milne Edwards & Haime, 1857, Anthus cervinus (Pallas, 1811), Regulus ignicapilla (Temminck, 1820), Ardea purpurea Linnaeus, 1766)", "Continent is one of (Europe)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 428868 records from 64 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0310645-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences